HUBUNGAN KETERAMPILAN MEMBACA PEMAHAMAN NASKAH DRAMA DENGAN KETERAMPILAN MENULIS NASKAH DRAMA SISWA KELAS VIII SMP NEGERI 13 PADANG - Zulfikarni, Mira Elfiza, Andria Catri Thamsin, (Universitas Negeri Padang, 2017)
The purpose of this study consists of three things as follows. First, describe the skill of reading comprehension of drama script of class VIII students of SMP Negeri 13 Padang. Second, describe the skill of writing drama script of class VIII students of SMP Negeri 13 Padang. Third, analyze the skill of reading comprehension of drama script with skill of writing script of drama of student of class VIII SMP Negeri 13 Padang. Based on the results of data analysis concluded three things as follows. First, the skill of reading comprehension of play script of class VIII drama of SMP Negeri 13 Padang is in Good qualification (B) with average count 80,65. Second, the skill of writing the script of the drama of class VIII students of SMP Negeri 13 Padang is in Good qualification (B) with average count 81,67. Third, based on t-test results, the alternative hypothesis (H1) is accepted at 95% confidence level and degrees of freedom (dk) = n-2 because tcount> ttable (6.54> 1.70).Kata Kunci:Â korelasi, keterampilan membaca pemahaman naskah drama, menulisÂ naskah drama.